PROPORSI MOCAF DAN TEPUNG LARUT DENGAN PENAMBAHAN MALTODEKSTRIN PADA PENGOLAHAN COOKIES - Indra Agustanugraha Pramadi; Fungki Sri Rejeki; Tri Rahayuningsih; Endang Retno Wedowati (JURNAL AGROTEKNOLOGI, 2019)
Cookies is snacks made from wheat flour. Wheat flour contains gluten which cannot be consumed by people with celiac diseases and autism. MOCAF is a modification of cassava flour that changes functional properties and can be used to substitute wheat flour. The use of MOCAF produces cookies that are hard-textured, so it is necessary to add arrowroot flour. Arrowroot flour was chosen because it contains low calories and non-gluten. Maltodextrin was used as maker crispy and binder ingredients. The research aimed were to determine the effect of MOCAF and arrowroot flour proportion and maltodextrin addition to the cookies characteristics, and determine the best alternative cookies processing. This research used factorial randomized block design with two factors. First factor was MOCAF and arrowroot flour proportion (T) with three levels (T1=100%:0%, T2=95%:5%, T3=90%:10%) and second factor was maltodextrin concentration (M) with three levels (M1=2%, M2=4%, M3=6%). Parameters research were proximate analysis, calories, yield, ability to swell, and organoleptic properties. The alternative selection used Expectation Value method. The results showed that there were no interactions between treatments on all research parameters, T treatment was significantly different on all organoleptic parameters, M treatment was significantly different on yield, fat and carbohydrate content, organoleptic properties, and the chosen treatment was T2M3 with expectation value was 8.21. Keywords: arrowroot flour, maltodextrin, MOCAF, non-gluten cookies